Acute serotonergic treatment changes the relation between anxiety and HPA-axis functioning and periaqueductal gray activation - Hestermann, Dietmar (2015)
Serotonergic (5-HT) drugs are widely used in the clinical management of mood and anxiety disorders. However, it is reported that acute 5-HT treatment elicits anxiogenic-like behavior. Interestingly, the periaqueductal gray (PAG), a midbrain structure which regulates anxiety behavior - has robust 5-HT fibers and reciprocal connections with the hypothalamic-pituitary-adrenal (HPA) axis. Although the HPA axis and the 5-HT system are well investigated, the relationship between the stress hormones induced by 5-HT drug treatment and the PAG neural correlates of the behavior remain largely unknown. In this study, the effects of acute and chronic treatments with buspirone (BUSP) and escitalopram (ESCIT) on anxiety-related behaviors were tested in an open-field (OF). The treatment effects on PAG c-Fos immunoreactivity (c-Fos-ir) and corticosterone (CORT) concentration were measured in order to determine the neural-endocrine correlates of anxiety-related behaviors and drug treatments. Our results demonstrate that acute BUSP and ESCIT treatments induced anxiogenic behaviors with elevation of CORT compared to the baseline. A decrease of c-Fos-ir was found in the dorsomedial PAG region of both the treatment groups. Correlation analysis showed that the CORT were not associated with the OF anxiogenic behavior and PAG c-Fos-ir. No significant differences were found in behaviors and CORT after chronic treatment. In conclusion, acute BUSP and ESCIT treatments elicited anxiogenic response with activation of the HPA axis and reduction of c-Fos-ir in the dorsomedial PAG. Although no correlation was found between the stress hormone and the PAG c-Fos-ir, this does not imply the lack of cause-and-effect relationship between neuroendocrine effects and PAG function in anxiety responses. These correlation studies suggest that the regulation of 5-HT system was probably disrupted by acute 5-HT treatment.